О распределении напряжений около горных выработок - Гайдайчук, В.В.; Кошель, В.И.; Луговой, П.З. (Прикладная механика, 2010)
Using the finite element method, the stress state around the arched mine working is determined. The working includes the mineral-bed. An analysis testifies the essential effect both presence of the mineral-bed, and its bedding direction on the stress state abound the mine working. The concrete recommendations are formulated for design of mine working reinforcement. Методом cкінченних елементів визначено напружений стан навколо склепінчас-
тих гірничих виробок, через які проходить пласт корисної копалини. Аналіз отриманих результатів
свідчіть про значний вплив як наявності пласта, так і напрямку його залягання на напружений стан
навколо виробки.